Strategic Implementation Of Speech Functions On The Automotive Billboard Texts - Muhammad Hasyimsyah Batubara (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2021)
This research aims to describe the category and derive dominantly used speech functions in the automotive billboard texts. The study used a descriptive qualitative method. Data is automotive billboard texts around the Medan city, and it is collected by applying documentary techniques. The finding describes there are three speech functions available used in automotive billboard texts. They are ten statements (76. 9%), one offer (7. 7%), and two commands (15. 4%), and there is no question in this domain. The statement model used as the stand-out one is compatible with the essential functions of commercial billboard texts, the viewer estimated only concisely saw the images and display of the billboard texts with 5-7 seconds when they were driving. Hence, the power of speech function and the language used must be effective, efficient, and capable of persuading or hypnotizing readers to take consumptive actions against products advertised by manufacturers.